THE EFFECT OF CLIMATE ON TOTAL PHENOLICS IN MACROTYLOMA UNIFLORUM, VIGNA UNGUICULATA, CINNAMOMUM ZEYLANICUM AND MENTHA PIPERITA USING SPECTROPHOTOMETER - Saxena, Vasundhara; Kk, Chagti (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Polyphenolic compound which is proven as antioxidants and possesses a chemo - protective potential are found in leaves, flowers, fruits, and bark. The aim of the study was to estimate the amount of tannins present in these drugs using Folin-Denis method. This study was conducted to evaluate the variations in the total amount of secondary metabolites (poly-phenolic) during summer and winter seasons in the leaves of four important valuable medicinal plants, viz., Macrotyloma uniflorum, Vigna unguiculata, Cinnamomum zeylanicum, and Mentha piperita using ultravioletvisible spectrophotometry. Methods: Tannin contents of plants were measured by Folin-Denis method. Tannin-like compounds reduce phosphotungstomolybdic acid in alkaline solution to produce a highly colored blue solution, the intensity of which is proportional to the amount of tannins present. The intensity is measured in a spectrophotometer at 650 nm. Results: The concentration was almost same for Mu1 and Mu2 plant with little effect of seasonal variations and at the same place it was found to be maximum in Cz1. The concentration curve for tannic acid was determined, and the correlation coefficient was calculated and was found to be 1 which indicates the good linearity between the concentration and the absorbance. Conclusion: The maximum amounts of secondary metabolites (poly-phenolic) were observed during summer, while minimum in winter season with an exception of Mu2 plant. Thus, this study was used as one of the parameters for standardization of medicinal plants. Keywords: Macrotyloma uniflorum, Vigna unguiculata, Cinnamomum zeylanicum, Mentha piperita tannins, Total phenolics, Folin-Denis method.